Main Quality of Life Assessment Questions: an integrative review (Research, Society and Development, 2022)
To investigate the factors which are the main instruments used to assess quality of life and which are their applications. bibliographic study of the integrative literature review type, a survey was carried out in the Scielo and VHL databases. 13 scientific articles were analyzed from 2017 to 2022. The following descriptors were used: Quality of Life; Quality of Life Indicators; Evaluation of Programs and Instruments and Research. Werr identified 326 studies were in the databases. After eliminating 86 duplicate articles, 240 articles were selected. Of these, 65 were excluded after analyzing the titles and abstracts. Of the 175 eligible articles, they were excluded for the following reasons: 50 were not available in full; 48 did not meet the time frame; 37 did not assess the use of QOL questionnaires and 27 studies were review studies. In the end, 13 studies were included in the integrative review. In this integrative review, it was identified that the main questionnaires used to assess the level of quality of life are currently: WHOQOL-100; WHOQOL-bref; SF-36 and TQWL-42. It was noticed that each one is used for a certain type of public, as it is thus able to better cover the characteristics of the population studied. It was also seen that almost all of these questionnaires were based on the WHOQOL-bre, which was created by the World Health Organization, with a view to valuing the individual's perception of their QOL.